Determination of Lactoferrin Using High-Frequency Piezoelectric Quartz Aptamer Biosensor Based on Molecular Bond Rupture - Haizhi Wu; Shihui Si; Zheng Li; Jiayou Su; Shangguan Jia; Hao He; Chengcheng Peng; Tongqiang Cheng; Qian Wu (Molecules)
In this study, an aptamer biosensor for detecting lactoferrin (LF) was developed using piezoelectric quartz-induced bond rupture sensing technology. The thiol-modified aptamer I was immobilized on the gold electrode surface of the quartz crystal microbalance (QCM) through an Au-S bond to specifically bind LF. It was then combined with aptamer–magnetic beads to amplify the mass signal. The peak excitation voltage was 8 V at the resonance frequency for the 60 MHz gold-plated quartz crystal. When the molecular bond cracking process occurred, the aptamer–magnetic beads combined on the surface of the piezoelectric quartz were removed, which resulted in an increase in quartz crystal resonance frequency. Therefore, the specific detection of LF can be realized. Under optimized experimental conditions, the linear range for LF was 10–500 ng/mL, the detection limit (3σ) was 8.2 ng/mL, and the sample recoveries for actual milk powder samples ranged from 97.2% to 106.0%. Compared with conventional QCM sensing technology, the signal acquisition process of this sensing method is simple, fast, and easy to operate.